Pembentukan Indeks Emisi Gas Rumah Kaca dan Strategi Menuju Net Zero Emission Kabupaten/Kota di Pulau Jawa dalam Mendukung Indonesia Emas 2045 - Kautsar, Syahrizal; Ridwansyah, Rizki Riza; Priscilla, Nindia (Seminar Nasional Official Statistics, 2024)
Net zero emissions is one of the visions that Indonesia wants to achieve in the RPJPN 2025-2045. This is done to prevent global warming due to increased concentrations of greenhouse gases. In 2023, 5 out of 6 provinces on the island of Java have the lowest Air Quality Index, which indicates the existence of greenhouse gas problems on the island of Java. This research aims to form a greenhouse gas emissions index with more complex forming indicators using factor analysis and then connecting it with socio-economic indicators using linear regression analysis. This research uses data from districts/cities on the island of Java in 2023 sourced from Sentinel-5P satellite imagery, MERRA-2, and BPS. The research results show that 15 cities have high emissions, 66 cities have medium emissions, and 38 cities have low emissions. In addition, per capita expenditure, population density, and industrial sector share can increase greenhouse gas emissions, while average years of schooling can reduce greenhouse gas emissions.